TRF2 positively regulates SULF2 expression increasing VEGF-A release and activity in tumor microenvironment - Pasquale Zizza; Roberto Dinami; Manuela Porru; Chiara Cingolani; Erica Salvati; Angela Rizzo; Carmen D’Angelo; Eleonora Petti; Carla Azzurra Amoreo; Marcella Mottolese; Isabella Sperduti; Angela Chambery; et al. (2019)
The telomeric protein TRF2 is overexpressed in several human malignancies and contributes to tumorigenesis even though the molecular mechanism is not completely understood. By using a high-throughput approach based on the multiplexed Luminex X-MAP technology, we demonstrated that TRF2 dramatically affects VEGF-A level in the secretome of cancer cells, promoting endothelial cell-differentiation and angiogenesis. The pro-angiogenic effect of TRF2 is independent from its role in telomere capping. Instead, TRF2 binding to a distal regulatory element promotes the expression of SULF2, an endoglucosamine-6-sulfatase that impairs the VEGF-A association to the plasma membrane by inducing post-synthetic modification of heparan sulfate proteoglycans (HSPGs). Finally, we addressed the clinical relevance of our findings showing that TRF2/SULF2 expression is a worse prognostic biomarker in colorectal cancer (CRC) patients.